Surface Solar Extremes in the Most Irradiated Region on Earth, Altiplano - Cordero, Raul R.; Feron, Sarah; Damiani, Alessandro; Sepulveda, Edgardo; Jorquera, Jose; Redondas, Alberto; Seckmeyer, Gunther; Carrasco Cerda, Jorge Fernando; Rowe, Penny; Ouyang, Zutao (My University, 2023)
Satellites have consistently pointed to the Altiplano of the Atacama Desert as the place on Earth where the world's highest surface irradiance occurs. This region, near the Tropic of Capricorn, is characterized by its high elevation, prevalent cloudless conditions, and relatively low concentrations of ozone, aerosols, and precipitable water. Aimed at studying the variability of the surface solar irradiance and detecting atmospheric composition changes in the Altiplano, an atmospheric observatory was set up in 2016 at the northwestern border of the Chajnantor Plateau (5,148 m MSL, 22.95&DEG;S, 67.78&DEG;W, Chile). Here, we report on the first 5 years of measurements at this observatory that establish the Altiplano as the region that receives the highest-known locations. We found that the global horizontal shortwave (SW) irradiance on the plateau is on average 308 W m-2 (equivalent to an annual irradiation of 2.7 MWh m-2 yr-1, the highest worldwide). We also found that forward scattering by broken clouds often leads to intense bursts of SW irradiance; a record of 2,177 W m-2 was measured, equivalent to the extraterrestrial SW irradiance expected at approximately 0.79 astronomical units (AU) from the Sun. These cloud-driven surface solar extremes occur on the Chajnantor Plateau at a frequency, intensity, and duration not previously seen anywhere in the world, making the site an ideal location for studying the response of photovoltaic (PV) power plants to periods of enhanced SW variability.
Keywords: atmosphere; south america; extreme events; shortwave radiation; surface observations; renewable energy